A novel opposition-based tuned-chaotic differential evolution technique for techno-economic analysis by optimal placement of distributed generation. Issue 2 (1st February 2020) - Kumar, Sajjan; Mandal, Kamal K.; Chakraborty, Niladri
ABSTRACT: Optimal placement of distributed generation (DG) units in a radial distribution network can reduce the system losses, improve the voltage profile of the network and thereby maximize the techno-economic benefits. The present problem considers various indices, namely the cost index, voltage deviation index and line flow capacity index, with several equality and inequality constraints, to analyse the techno-economic benefits. An opposition-based tuned-chaotic differential evolution (OTCDE) technique is proposed to avoid premature convergence. This technique uses an opposition-based scheme for initialization and logistic mapping to generate chaotic sequences within the specified range for the mutation factor, because wrong parameter selection may lead to premature convergence and even stagnation. The proposed algorithm has been applied on IEEE 33-bus, 69-bus and 118-bus radial distribution systems to verify its effectiveness. By several statistical analyses, it is observed that the proposed technique outperforms other newly proposed metaheuristic techniques.